Evaluation of response, damage, and repair cost of reinforced concrete super high‐rise buildings subjected to large‐amplitude earthquakes - Kazutaka Shirai; Hajime Okano; Yuu Nakanishi; Takashi Takeuchi; Katsunori Sasamoto; Miwa Sadamoto; Koichi Kusunoki (Japan Architectural Review)
Abstract The present study developed a method for evaluating the response, damage, and repair cost of super high‐rise reinforced concrete (RC) buildings subjected to large‐amplitude earthquakes. The response was numerically assessed using three‐dimensional 40‐story RC frame models under the predicted seismic motions of earthquakes along the Sagami Trough and Nankai Trough considering the effects of slip behavior, slab cooperative width, and stud‐type dampers. Even when the RC mainframe exhibited slip, the peak response deformation was effectively reduced by the friction dampers incorporated into each story. A probabilistic approach based on fragility was used to evaluate the damage and repair cost of the building models. The distributions of the damage states and repair cost for each story under the predicted seismic motions of earthquakes along the Sagami Trough and Nankai Trough were determined, and the total repair cost in relation to the total construction cost was evaluated. The occurrence of damage state 1 had a relatively large effect on the evaluated total repair cost under the evaluation conditions used in this study. A nonlinear relationship was observed between the input magnification and the total repair cost. The friction dampers reduced the damage and total repair cost.